(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
A variety of alternative energy sources are being investigated for hybrid cars as a means of refueling the world’s depleted petroleum supply. The usage of fossil fuel in cars is becoming a growing source of worry due to its negative environmental consequences. Battery, fuel cell (FC), super capacitors (SC), and photovoltaic cell (PV) are among the sources being investigated for automotive applications. These renewable energy sources may be used to create a hybrid electric vehicle (HEV) for the future generation of mobility. This article examines many elements and methods of HEVs, including energy management systems (EMS), power conditioning, and propulsion systems. Other HEV-related fields including DC machines and automotive systems are also covered. Different types of models and algorithms developed from simulation and experiment are thoroughly described. The table summarizes the performance of different HEV system combinations, along with pertinent references. Various academics have produced a thorough assessment of hybrid electric vehicles, including their source combinations, models, and energy management systems (EMS). Following a thorough examination, it was shown that current technologies are more or less capable of performing HEV effectively; nevertheless, dependability and intelligent systems are still lacking. As a result, numerous aspects, difficulties, and concerns with the next generation hybrid car have been highlighted in this study.